2010
DOI: 10.1093/ndt/gfq409
|View full text |Cite
|
Sign up to set email alerts
|

Is left ventricular hypertrophy a powerful predictor of progression to dialysis in chronic kidney disease?

Abstract: LVH proved to be the strongest predictor of the risk of progression to dialysis in non-diabetic CKD, especially among patients with less advanced renal dysfunction. Regardless of whether it is a simple marker or a pathogenetic factor, LVH encompasses all factors possibly affecting renal and general outcome in CKD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 30 publications
2
25
0
1
Order By: Relevance
“…This finding, which is consistent with previous findings both in hypertensive men 7 and in subjects with stages 3 and 4 CKD, 8,9 extends and encompasses those findings, in that it was made in a very large cohort of patients that included both men and women, and is representative of a hypertensive population managed with primary care in a western country. 12 The relationship that we found between LVH and worsening of renal function points out the role of subclinical cardiac damage in predicting future adverse renal outcome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding, which is consistent with previous findings both in hypertensive men 7 and in subjects with stages 3 and 4 CKD, 8,9 extends and encompasses those findings, in that it was made in a very large cohort of patients that included both men and women, and is representative of a hypertensive population managed with primary care in a western country. 12 The relationship that we found between LVH and worsening of renal function points out the role of subclinical cardiac damage in predicting future adverse renal outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, these data were not available in the database of the retrospective study by Tsioufis, 7 whereas they predicted renal disease progression in the small cohort of Chen, 9 and were not associated with adverse renal outcome in another, similar cohort of CKD patients. 8 We speculate that the strong pathogenetic role of LVH may have somewhat masked the effect of proteinuria in predicting adverse renal outcome, because none of the other studies that emphasized the predictive role of proteinuria on renal outcome evaluated cardiac size or function. [29][30][31][32] Lastly, no data on BP behavior or antihypertensive medications were available at the time of follow-up of our study cohort.…”
Section: Discussionmentioning
confidence: 94%
“…Association between LVH and renal outcomes. Paoletti et al [13] studied 144 patients with CKD stage 3-4 to evaluate the role of LVH in predicting progression to dialysis, and found that an increased LVMI was independently associated with progression to dialysis and the combined endpoints of dialysis or morality. The authors concluded that the same pathogenetic factors were responsible for both kidney damage and increases in LV wall thickness and internal LV dimensions.…”
Section: Echocardiography Parametersmentioning
confidence: 99%
“…15,16 Patients with LVH may have decreased myocardial contractility and impaired LV diastolic function, 17 which may have a progressive effect on renal function with an adverse outcome. 18,19 Iwashima et al 14 had evaluated the effect of a combination of UA and LVMI on five cardiovascular outcomes in 619 patients with essential hypertension. They found that the combination of hyperuricemia and LVH was a predictor of cardiovascular outcomes.…”
mentioning
confidence: 99%